The Effect of Gargling with Turmeric Solution on the Gingival Index in Patients with Gingivitis - Yenti, Aflinda; Sukanti, Eka; Damhuji, Damhuji; Eriyati, Eriyati; Faisal, Muhammad (Yayasan Ahmad Mansyur Nasirah, 2025)
Women are generally more susceptible to dental and oral diseases, one of which is gum inflammation (gingivitis), caused by bacterial plaque infection. Untreated gingivitis in adolescents can lead to further complications in the periodontal tissues. Gingivitis treatment can be carried out by gargling with traditional ingredients that are safe for adolescents and do not cause harmful side effects. One natural traditional ingredient that can be used is a turmeric solution mouthwash, which contains antibacterial, anti-inflammatory, and antioxidant properties. This study aims to determine the changes in the gingival index of respondents suffering from gingivitis after gargling with turmeric solution at the Department of Dental Health, Poltekkes Kemenkes Padang. The research employed a quasi-experimental method by administering a turmeric solution gargle to respondents with gingivitis, and then examining their gingival index after three days of use. The study population consisted of all students at the Department of Dental Health, Poltekkes Kemenkes Padang. The sample was taken from students in the department using a judgement sampling technique. Data were analysed using a paired t-test. The results showed that before gargling with turmeric solution, the most common gingival index categories among respondents were moderate and severe (each 44.4%), whereas after gargling, the majority fell into the mild category (55.5%). The paired t-test yielded a p-value of 0.001. In conclusion, there is a significant effect of gargling turmeric solution on gingival index in patients with gingivitis. It is recommended for further research to research the optimal formulation and concentration of turmeric solution, as well as the safety of its long-term use for adolescents and other age groups.